(untitled) (JURNAL IBU DAN ANAK, 2022)
The inability to release breast milk is a problem experienced by breastfeeding mothers. One of the causes of non-smooth milk production is a decrease in milk production on the first day after giving birth, which can be caused by a lack of the hormone Oxytocin which plays a very important role in the smooth production of breast milk. To express breast milk requires an effort in the form of Oxytocin massage. on Postpartum Mothers in the Working Area of ​​Lumut Health Center, Central Tapanuli Regency in 2021 this type of research is quantitative with a Quasy-experimental design. The population in this study were all postpartum mothers who experienced irregular breastfeeding in the Lumut Health Center Work Area, Central Tapanuli Regency in 2021 with a sample of 19 mothers with the Wilcoxon test. Postpartum Mother. Statistical test using Wilcoxont ​​statistical test. The results of this study showed that the average smoothness of breast milk in postpartum mothers before Oxytocin massage was 4.6316 (Substandard), while the average smoothness of breast milk in postpartum mothers after Oxytocin massage was 8.0526 (Smooth). The Wilcoxon test shows that the p value = o,oo <a (0.05) so that Ha is accepted. There is an effect of Oxytocin massage on the smoothness of breastfeeding in the working area of ​​the Lumut Health Center, Lumut District, Central Tapanuli Regency in 2021